Methodology of innovative management - Akramova Aziza Abduvohidovna (Global Scientific Publishing, 2023)
The concept of "management" is interpreted as an influence on various objects, it has the purpose of regulation, improvement and development. The article covers the basics of management, the development of innovative management, its theoretical concepts, ways to improve evolutionary management and their methodology.
Keywords: Innovative management system; circular network